2018
DOI: 10.1007/s10877-018-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine increases cardiac output by raising cardiac preload in patients with anesthesia induced hypotension

Abstract: Induction of general anesthesia frequently induces arterial hypotension, which is often treated with a vasopressor, such as phenylephrine. As a pure α-agonist, phenylephrine is conventionally considered to solely induce arterial vasoconstriction and thus increase cardiac afterload but not cardiac preload. In specific circumstances, however, phenylephrine may also contribute to an increase in venous return and thus cardiac output (CO). The aim of this study is to describe the initial time course of the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 26 publications
(33 reference statements)
4
61
1
Order By: Relevance
“…30 In this context, phenylephrine, metaraminol and noradrenaline infusions are all potential candidates for peripheral short term infusion strategies. 31,32 Ephedrine can also be used by infusion and is effective, though it may lead to more episodes of dysrhythmia. 33 Phenylephrine has been the agent of choice for treating spinal anaesthesia induced hypotension due to its primary vasoconstrictor action, while ephedrine preferentially acts to improve cardiac output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In this context, phenylephrine, metaraminol and noradrenaline infusions are all potential candidates for peripheral short term infusion strategies. 31,32 Ephedrine can also be used by infusion and is effective, though it may lead to more episodes of dysrhythmia. 33 Phenylephrine has been the agent of choice for treating spinal anaesthesia induced hypotension due to its primary vasoconstrictor action, while ephedrine preferentially acts to improve cardiac output.…”
Section: Resultsmentioning
confidence: 99%
“…34 However, a recent prospective study on the effects of phenylephrine for anaesthesia induced hypotension showed that it was effective at increasing cardiac output in patients who were relatively hypovolemic. 31 Many patients in the hip fracture cohort will have a degree of physiological beta-blockade secondary to age-related autonomic dysfunction, making alpha-1 adrenoceptor agonists the treatment of choice. 34,35 It is not clear whether hypotension is more reliably prevented in high-risk patients by administering intermittent boluses purely when deemed appropriate by the clinician, or by using a continuous infusion.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in venous tone can change the relative proportions of the unstressed and stressed volumes. For example, alpha adrenergic receptor agonists may increase venous tone and thus increase the stressed volume (and simultaneously lower the unstressed volume), increasing venous return to the heart, raising SV and CO. (Kalmar et al, 2018;Hamzaoui et al, 2010) What is fluid responsiveness? How do we define it, is there variation in proposed definitions, and is there variation from those in clinical practice?…”
Section: Hypervolemiamentioning
confidence: 99%
“…They showed that phenylephrine administration resulted in an increase in cardiac preload, as illustrated by the decrease of both static and dynamic markers of cardiac preload, which increased CO despite the increase in LV afterload, reflected by an increased systemic vascular resistance [1]. The authors suggest the increase in cardiac preload to be the result of an increase in venous return, as they found the pressure gradient driving the venous return to be increased to a greater extent than the resistance to the venous return [6,7].…”
mentioning
confidence: 98%
“…In this issue, Kalmar et al elegantly depicted the chronology of the haemodynamic effects, caused by a single administration of phenylephrine, in preload-dependent patients with anaesthesia-induced hypotension. For this purpose, the authors assessed several distinct haemodynamic and nonhaemodynamic indices [6]. They showed that phenylephrine administration resulted in an increase in cardiac preload, as illustrated by the decrease of both static and dynamic markers of cardiac preload, which increased CO despite the increase in LV afterload, reflected by an increased systemic vascular resistance [1].…”
mentioning
confidence: 99%